Persistent peri‐Heptacene: Synthesis and In Situ Characterization. (12th May 2021) - Ajayakumar, M. R.; Ma, Ji; Lucotti, Andrea; Schellhammer, Karl Sebastian; Serra, Gianluca; Dmitrieva, Evgenia; Rosenkranz, Marco; Komber, Hartmut; Liu, Junzhi; Ortmann, Frank; Tommasini, Matteo; Feng, Xinliang
Abstract: n‐peri‐Acenes (n‐PAs) have gained interest as model systems of zigzag‐edged graphene nanoribbons for potential applications in nanoelectronics and spintronics. However, the synthesis of n‐PAs larger than peri‐tetracene remains challenging because of their intrinsic open‐shell character and high reactivity. Presented here is the synthesis of a hitherto unknown n‐PA, that is, peri‐heptacene (7‐PA ), in which the reactive zigzag edges are kinetically protected with eight 4‐tBu‐C6 H4 groups. The formation of 7‐PA is validated by high‐resolution mass spectrometry and in situ FT‐Raman spectroscopy. 7‐PA displays a narrow optical energy gap of 1.01 eV and exhibits persistent stability ( t 1/2 ≈25 min) under inert conditions. Moreover, electron‐spin resonance measurements and theoretical studies reveal that 7‐PA exhibits an open‐shell feature and a significant tetraradical character. This strategy could be considered a modular approach for the construction of next‐generation (3  N +1)‐PAs (where N ≥3). Abstract : The synthesis of the hitherto unknown peri ‐heptacene 7‐PA is demonstrated by a rational molecular design strategy in which the reactive zigzag edges are kinetically protected. The formation of 7‐PA is validated by high‐resolution mass spectrometry and in situ FT‐Raman spectroscopy. The open‐shell 7‐PA displays a narrow optical energy gap of 1.01 eV and exhibits a persistent stability (half‐life ≈25 min) under inert conditions.